(untitled) (Research, Society and Development, 2021)
Objective: To compare the resilience and depression scores in patients with head and neck squamous cell carcinoma (HNSCC) undergoing surgical treatment at different times of treatment and to correlate these variables. Methodology: This is a cohort study, developed with 28 patients diagnosed with HNSCC, undergoing surgical treatment and followed up preoperatively (T1), four to six weeks (T2) and six months after the end of treatment (T3). The Mini Mental State Examination (MMSE), the Resilience Scale and the Beck Depression Inventory were applied in three moments. Results: Comparing resilience, its domains and depression in the three stages, there was no significant difference. A positive correlation was noted between resilience and depression. Conclusion: Given the relationship between resilience and depression observed, it is suggested that these variables be evaluated in this group of patients, to help the team to infer which of them can benefit from an early intervention, to work on strategies to reduce levels of depression and increase resilience, contributing to treatment success.